Ultrastructural analysis of glands located in the wall of the congenital fistulae of the lower lip of patients with Van der Woude syndrome - Onofre, Mirian Aparecida [UNESP]; Brosco, Heli Benedito; Taga, Rumio (Faculdade De Odontologia De Bauru - USP, 2003)
The objective of the present study was to evaluate the glands of wall of congenital fistulae of the lower lip with the transmission electron microscope in order to characterize their microstructural pattern. Thin section of Araldite resin embedded congenital fistulae of the lower lip of four patients with Van der Woude syndrome from the Hospital de Reabilitação de Anomalias Craniofaciais da Universidade de São Paulo, Bauru, SP, were analyzed with a transmission electron microscope. The results showed that the glands were mostly made by typical mucous acini exhibiting, with certain frequency, myoepithelial cells surrounding them. In some of lobules, a few acini smaller than the typical mucous, showed granules of moderate electron density or containing a dense core or exhibiting small dense spherule and predominance granular material. These granules resemble to described recently by others in various human minor salivary glands. We concluded that glands associated with congenital fistula of lower lip of patients with Van der Woude syndrome, in spite of being located in vermilion border of the lip, showed at the transmission electron microscope characteristics of labial minor salivary gland, i.e, are mostly mucous with a few seromucous units, while typical seromucous demilunes are not present.

O objetivo do presente estudo foi avaliar a ultraestrutura de glândulas da parede de fístula congênita de lábio inferior ao microscópio eletrônico de transmissão para caracterizar seu padrão microestrutural. Deste modo, as fístulas congênitas de 4 pacientes com a síndrome de Van der Woude do Hospital de Reabilitação de Anomalias Craniofaciais da Universidade de Sâo Paulo, Bauru, SP, foram processadas para inclusão em resina Araldite e os cortes finos foram analisados no microscópio eletrônico de transmissão. Os resultados mostraram que as glândulas estavam constituídas por ácinos mucosos típicos exibindo com certa freqüência células mioepiteliais ao seu redor. Em alguns lóbulos, foram observados em pequeno número, ácinos menores que o mucoso típico, exibindo células com grânulos de moderada eletron-densidade contendo um corpo denso ou uma pequena esférula densa no interior de um material predominante granular. Estes grânulos lembravam os descritos recentemente em glândulas salivares labiais humanas. Em vista dos resultados obtidos concluímos que as glândulas associadas com a fístula congênita de lábio inferior de pacientes com a síndrome de Van der Woude, apesar de estarem localizadas no vermelhão do lábio, mostraram ao microscópio eletrônico de transmissão características de glândula salivar labial, i.e., são predominantemente mucosos com poucas unidades seromucosas, mas semiluas seromucosas típicas não estão presentes.
Análise ultra-estrutural das glândulas localizadas na parede da fístula congênita de lábio inferior de pacientes com a síndrome de Van der Woude
Keywords: Fistula; Lip diseases; Van der Woude syndrome; Fístula; Doença labial; Sindrome de Van der Woude